Vibrational spectra of three new diarsenates containing scandium(III) - Baran, Enrique José (2006)
The powder Fourier transform (FT) infrared and Raman spectra of the new isotypic diarsenates RbScAs2O7, TlScAs2O7, and (NH4)ScAs2O7 are discussed with a factor group analysis, on the basis of their known structural characteristics. The spectroscopic behavior clearly reflects all the structural peculiarities and also confirms the rotational quenching of the NH4 + cation in (NH4) ScAs2O7. The crystal structure of TlScAs2O7 is also reported for the first time and is briefly discussed.